2004
DOI: 10.1111/j.1741-2358.2004.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory performance in 80‐year‐old individuals

Abstract: Most of the 80-year-old individuals recovered their masticatory ability with the assistance of prostheses. Several individuals with 20 or more remaining teeth or without removable dentures present in both jaws had a high score for bite forces and masticatory abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 20 publications
5
51
1
3
Order By: Relevance
“…Bite forces, the total contact and surface areas have also been found to be higher in dentate men than women (7,25). However, no gender differences in bite force and masticatory performance was found among complete denture wearers (25).…”
Section: Gendermentioning
confidence: 86%
“…Bite forces, the total contact and surface areas have also been found to be higher in dentate men than women (7,25). However, no gender differences in bite force and masticatory performance was found among complete denture wearers (25).…”
Section: Gendermentioning
confidence: 86%
“…Maintaining masticatory ability is important in maintaining daily life activities and social participation 9) . Most 80 year-old elderly persons would recover their masticatory ability with the assistance of a prosthesis 22) . A future goal is for the elderly aged 80 years to have 24 teeth or more 21) .…”
Section: Discussionmentioning
confidence: 99%
“…3) Exercise for salivary glands -Hold breath and swallow saliva (3 times) -While keeping mouth open, utter "pa", "ta", "ka", "ra", and "panda no takaramono" in a loud voice (3 times) teeth (Tsuga et al 1998), and individuals with 20 or more remaining teeth in both jaws were reported to have high scores for bite force and masticatory ability (Tatematsu et al 2004). Decrease in swallowing ability with age may lead to undernutrition, dehydration, and occasionally aspiration pneumonia (Finestone et al 1995;Reza et al 2006).…”
Section: Discussionmentioning
confidence: 99%